Pengaruh Motivasi Dan Lingkungan Belajar Terhadap Hasil Belajar Mata Kuliah Akuntansi Manajemen Pada Mahasiswa Pendidikan Akuntansi Universitas Muhammadiyah Surakarta Angkatan 2012 - Ayu Hartono, Diah, Prof. Dr. Harsono. SU (2017)
The purpose of this study was to determine: 1) .Pengaruh belajr motivation on learning outcomes of the course on Management Accounting Accounting Education students Forces Surakarta Muhammadiyah University, 2012. 2). Studying environmental influences on learning outcomes of the course to the students of Management Accounting Accounting Education Surakarta Muhammadiyah University, 2012. Forces 3). Effect of motivation and learning environment to the learning outcomes on student Management Accounting Accounting Education 2012 University of Muhammadiyah Surakarta Force. This study includes quantitative research. This study took place at the University of Muhammadiyah Surakarta. Data collection techniques by using questionnaires which have been tested by validity and reliability testing. The analysis technique used is multiple regression. Results of regression analysis regression equation; Y = 18.291 + 0,271X1 + 0,251X2, which means that the learning outcomes are influenced by motivation and learning environment, based on the analysis and discussion can be concluded that: 1) .Motivasi positive effect on student learning outcomes in Accounting Education Muhammadiyah University of Surakarta Force 2012. This can be seen by the results of multiple linear regression analysis (t test) is known thitung> ttable, namely 3.059> 1.984 and the significance value <0.05, namely 0.003 with the relative contribution of 49.6% and 11.7% effective contribution. 2). The learning environment has positive influence on student learning outcomes Accounting Education Universitas Muhammadiyah Surakarta Force 2012. This can be seen by the results of multiple linear regression analysis (t test) is known thitung> ttable, namely 4.768> 1.984 and the significance value <0.05, namely 0.003 with the relative contribution of 50.5% and 11.9% effective contribution. 3) .Motivasi and learning environment together positively to having an effect on student learning outcomes Accounting Education Universitas Muhammadiyah Surakarta Force 2012. This can be seen by the results of multiple linear regression analysis (F test) is known Fhitung> Ftable is 14 998> 3,07 with significant value <0.05 is 0.000. This shows bahwahasil study have the same tendency with the combination followed by an increase in motivation and learning environment. The coefficient of determination of 23.6%, which means that there is influence exerted by variable combinations of motivation and learning environment to the learning outcomes by 23.6%, while 76.4% are influenced by other factors not examined by the author.